ANALISIS PENGARUH JUMLAH PENDUDUK TERHADAP SALINITAS AIR TANAH DI WILAYAH PESISIR KARAWANG - Wida Riyanti; Sata Yoshida Srie Rahayu; Azis Kemal Fauzie (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2022)
The study carried out on April 2021 used an explorative correlational approach and aimed to identify the shallow groundwater quality in Karawang coastal area and to analyze the effect of population number on the groundwater salinity. Groundwater sampling was managed using systematic random grid sampling method by dividing the Karawang coastal area into 30 grids of a uniform size of 2 km × 7 km. The analysis of groundwater samples taken from public borewells obtained a result that the quality of groundwater in Karawang coastal area at 4 to 15-meter depth has an average salinity of 1,5 ppt and total dissolved solid (TDS) of 1491,6 mg/l. The population number data were collected by direct observation to the local community at the study sites aided by administrative data collected from the village authorities. Interpretation analysis of correlation and regression using SPSS showed a significantly positive interaction between population number and groundwater salinity (r = 0,717; p < 0,001). This positive relationship gives the tendency that the groundwater salinity will increase as the population number grows.